2009
DOI: 10.1080/00206810902951411
|View full text |Cite
|
Sign up to set email alerts
|

Origin and geodynamic evolution of late Cenozoic potassium-rich volcanism in the Isparta area, southwestern Turkey

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 106 publications
0
25
0
1
Order By: Relevance
“…A mantle component with a high 206 Pb/ 204 Pb signature was previously suggested to explain the origin of some strongly potassic rock suites in western Anatolia; however, based on its unradiogenic 87 Sr/ 86 Sr signature (which is referred to as an “intraplate” signature), this component has since been interpreted to reflect an asthenospheric origin with the possible contribution of carbonatitic fluids (Caran, ; Elitok et al, ; Platevoet et al, ; Prelević et al, ). However, no effort has yet been made to explain the highly radiogenic 206 Pb/ 204 Pb signature of this component, which appears to require long‐term isolation from the mantle convection.…”
Section: Heterogeneous Enrichment Of the Lithospheric Mantlementioning
confidence: 99%
See 1 more Smart Citation
“…A mantle component with a high 206 Pb/ 204 Pb signature was previously suggested to explain the origin of some strongly potassic rock suites in western Anatolia; however, based on its unradiogenic 87 Sr/ 86 Sr signature (which is referred to as an “intraplate” signature), this component has since been interpreted to reflect an asthenospheric origin with the possible contribution of carbonatitic fluids (Caran, ; Elitok et al, ; Platevoet et al, ; Prelević et al, ). However, no effort has yet been made to explain the highly radiogenic 206 Pb/ 204 Pb signature of this component, which appears to require long‐term isolation from the mantle convection.…”
Section: Heterogeneous Enrichment Of the Lithospheric Mantlementioning
confidence: 99%
“…However, regardless of the type of material involved and the processes envisioned, it has been suggested that subduction‐related metasomatic components share some common isotopic signatures (usually defined as “orogenic” signatures), which are represented by high 87 Sr/ 86 Sr and low 143 Nd/ 144 Nd values (Aldanmaz et al, ; Çoban et al, ; Ersoy & Palmer, ; Prelević et al, , ). On the other hand, melt compositions with distinctly low 87 Sr/ 86 Sr (<0.7040), high 143 Nd/ 144 Nd (>0.5128), and radiogenic 206 Pb/ 204 Pb values (defined as “anorogenic” signatures) have been interpreted to primarily reflect the involvement of melts from the convecting asthenospheric mantle (Dilek & Altunkaynak, ; Elitok et al, ; Ersoy & Palmer, ; Platevoet et al, ; Prelević et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium-rich magmatic rocks occur widely in different tectonomagmatic environments such as continental active margins, post-collisional magmatic arcs and within plate settings (e.g., Muller et al, 1992;Mitchell et al, 1994;Elitok et al, 2010;Eyuboglu, 2010;Lu et al, 2012). It is widely accepted that the late Cenozoic magmatism in the Mediterranean-Iran regions occurred in a post-collisional setting and resulted from partial melting of a subduction-related metasomatized sub-continental lithospheric mantle (e.g., Aldanmaz et al, 2000;Alici Sen et al, 2004;Altunkaynak and Genç, 2008;Altunkaynak et al, 2012;Ersoy et al, 2012a,b;Prelević et al, 2012).…”
Section: Geodynamic Implicationsmentioning
confidence: 99%
“…The temporal distribution of the magmatism in this region shows different phases of magma generation with distinct geochemical signatures mainly in the late Eocene, late Miocene and Plio-Quaternary Eyuboglu et al, 2010Eyuboglu et al, , 2011aEyuboglu et al, ,b,c,d,e, 2012Eyuboglu et al, , 2013a. Mantle-derived volcanic rocks with oceanic-island basalt (OIB)-like geochemical features with and/or without subduction fingerprints are commonly found in the Turkish-Iranian High Plateau (e.g., Aldanmaz et al, 2006;Dilek and Altunkaynak, 2009;Kheirkhah et al, 2009;Elitok et al, 2010;Allen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation